Aerospace series. Cable outlet accessories for circular and rectangular electrical and optical connectors. Stainless steel banding band, style Z, for attachment of individual and/or overall screens to cable outlets. Product standard Part 033, (8th November 2019) - British Standards Institution,
No abstract available